A Study of a BIPV/T Collector Prototype for Building Façade Applications. (November 2015) - Bigaila, Edvinas; Rounis, Efstratios; Luk, Peter; Athienitis, Andreas
Abstract: BIPV/T collectors incorporated into building envelopes can be used to replace conventional building materials in roofs, skylights or façades. A new design of BIPV/T solar air collector prototype for façade retrofit with emphasis on simplifying the integration into the building envelope was developed. Experimental results show, that this new design BIPV/T solar air collector reaches a comparable thermal efficiency with the one of unglazed thermal collectors (UTC) with additional photovoltaic electricity generation, leading to 10-15% higher combined efficiency. Custom thermal and fluid network numerical models were created to analyze their performance. Models were validated at the Concordia University Solar Simulator Lab. This paper presents the work done on testing, modeling and performance evaluation using 5-plot system for open loop photovoltaic/thermal solar air collectors.